The Influence of E-Servqual and Banking Service Quality on Customer Retention Intention in My-BCA Application with Customer Satisfaction as a Mediating Variable - Setyawan, Natanael Kris; Indira Rachmawati (International Journal of Integrative Sciences, 2024)
This study aims to analyze the influence of electronic service quality (e-SERVQUAL) and banking service quality (BSQ) on customer retention intention in the MyBCA application, with customer satisfaction acting as a mediator variable. Data was collected through a survey filled out by 384 respondents who are BCA customers and users of the MyBCA application. The analysis method used is Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that the dimensions of e-SERVQUAL (efficiency, fulfillment, system availability, and privacy) have a positive and significant effect on customer satisfaction. Similarly, the dimensions of BSQ (access, price, ease of use, service portfolio, reliability, and security) also show a positive and significant effect on customer satisfaction. Furthermore, customer satisfaction is proven to have a positive and significant impact on customer retention intention. This research contributes theoretically by expanding the understanding of factors influencing customer satisfaction and retention in the context of digital banking services. Practically, these findings provide insights for the developers of the MyBCA application and BCA management to enhance service quality to retain and increase customer loyalty